2015
DOI: 10.2147/ott.s81022
|View full text |Cite
|
Sign up to set email alerts
|

The clinical activity of arsenic trioxide, ascorbic acid, ifosfamide and prednisone combination therapy in patients with relapsed and refractory multiple myeloma

Abstract: This study aimed to investigate the activity of arsenic trioxide (As2O3) combined with ascorbic acid, ifosfamide, and prednisone chemotherapy in patients with repeatedly relapsed and refractory multiple myeloma (MM). Here, we retrospectively analyzed medical data of 30 MM patients showing progressive disease after receiving at least two previous lines of treatment including an immunomodulatory agent (thalidomide or lenalidomide) and a proteasome inhibitor. There were 19 men and eleven women, aged 54–73 (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our results are in keeping with the notion that both agents have favorable safety profiles in humans and do not induce significant myelosuppression. However, while low-dose ascorbate coupled to ATO has been used in pilot studies to treat AML [41] and multiple myeloma [42, 43], to the best of our knowledge no clinical studies combining ATO and high-dose ASC have been carried out in hematologic malignancies. Therefore, the presumed safety of the combination remains to be established in phase I studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in keeping with the notion that both agents have favorable safety profiles in humans and do not induce significant myelosuppression. However, while low-dose ascorbate coupled to ATO has been used in pilot studies to treat AML [41] and multiple myeloma [42, 43], to the best of our knowledge no clinical studies combining ATO and high-dose ASC have been carried out in hematologic malignancies. Therefore, the presumed safety of the combination remains to be established in phase I studies.…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate and median response duration were 74% and 17 months, respectively in this study. Other studies also reported synergistic effects of As 2 O 3 and AA combination in patients with RRMM [ 16 , 17 , 18 ]. As 2 O 3 and AA, in addition to bortezomib and dexamethasone combination can be an effective treatment strategy in these patients [19] .…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have also reported a decline in hematological parameters in both animal models and human populations following exposure to toxicants [31]. Earlier research has reported that the decrease in Hb levels could be attributed to the inactivation of the δ-aminolevulinic acid dehydrase enzyme, which plays a crucial role in Hb production [32,33]. Furthermore, this reduction in Hb might be a result of the apoptosis of plasma cells induced by As [34].…”
Section: Discussionmentioning
confidence: 97%